SPECIFIC CHARACTERISTICS OF THE ORGANIZATION OF OBLIGATION AUDITS IN MANUFACTURING ENTERPRISES - Nomozov Ilhomjon Ziyodullo ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, proposals and recommendations have been developed regarding the specific features of the audit of obligations in production enterprises.